DECOLONIZING WATER MANAGEMENT IN CANADA : THROUGH THE EMPOWERMENT OF INDIGENOUS WOMEN (Canadian Journal of Native Studies, 2026)
Indigenous women were traditionally recognized as “watercarriers” who played a leadership role equal to men in theircommunities. Since the Indian Act (1876), however, they havefaced “double discrimination,” as both Indigenous and women.This paper examines Attawapiskat First Nation’s watercrisis to highlight colonialism and government’s failure to coordinatea response at all levels resulting in much suffering,especially among Indigenous women and children. Drawingon the recent international WASH initiative and Anishinabekdecolonizing efforts, the paper underscores the significanceof a decolonial approach to water management based on theempowerment of Indigenous women and a coordinated governmentresponse to the protection of source water resources.